Novel Field Effect Transistor Fabrication Based on Non-Graphene 2D Materials. (7th June 2017) - Li, Yu-Tao; Zhao, Hai-Ming; Tian, He; Shao, Peng-Zhi; Xin, Xin; Cao, Hui-Wen; Deng, Ning-Qin; Yang, Yi; Ren, Tian-Ling
ABSTRACT: In this paper, field effect transistors (FET) based on different kinds of non-graphene materials are introduced, which are MoS2, WSe2 and black phosphorus (BP). Those devices have their unique features in fabrication process compared with conventional FETs. Among them, MoS2 FET shows better electrical characteristics by applying a SiO2 protective layer; WSe2 FET is fabricated based on a new low pressure chemical vapor deposition (LPCVD) method; BP FET acquires high on/off ratio and high hole mobility by using a simple dry transfer method. Those novel non-graphene materials inspire new design and fabrication process of basic logic device.